THE IMPACT OF PATIENT SATISFACTION ON PATIENT LOYALTY WITH THE MEDIATING EFFECT OF HOSPITAL IMAGE AT UKRIDA HOSPITAL - Reni Oktavina; Soegeng Wahyoedi; Wani Devita Gunardi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
The rapid advancement of technology and information has encouraged public organizations to develop innovative products and services that can meet the needs and desires of customers. Customers are thus pleased with the services they receive. Image and patient satisfaction are critical factors in influencing true loyalty in order to reuse and recommend to others. Data collected through questionnaires was analyzed using Structural Equation Modeling (SEM) and Partial Least Squares (PLS) software. The 100 participants in this study were outpatients who visited Ukrida Hospital more than once. According to the findings of the study, the direct effect of hospital image influences patient satisfaction and loyalty, whereas the indirect effect of hospital image can mediate patient satisfaction on patient loyalty. Ukrida Hospital desperately needs this to improve its image and increase patient satisfaction and loyalty.